Government Public Relations Strategy in Countering Public Policy Hoaxes in Cyberspace - Rojab Riswan Taufik (SEAN Institute, 2026)
The rapid development of cyberspace has triggered the high spread of hoaxes related to public policies, which have the potential to undermine public trust in local government. This study aims to analyze the Government Public Relations (GPR) strategy of the Banjar City Public Relations Office in countering public policy disinformation in cyberspace. The research method used was descriptive qualitative with a case study approach. Data collection was conducted through in-depth interviews with public relations practitioners, observations of official social media platforms, and archival documentation of cyber issue reports and clarification scripts. The results indicate that the cyber issue monitoring strategy was implemented through a combination of macro digital channels (Instagram and Facebook), micro channels (a network of information agents within the citizen WhatsApp Group), and the official complaint channel